2014
DOI: 10.1111/irv.12285
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant influenza H7 hemagglutinins induce lower neutralizing antibody titers in mice than do seasonal hemagglutinins

Abstract: BackgroundVaccines against avian influenza viruses often require high hemagglutinin (HA) doses or adjuvants to achieve serological titers associated with protection against disease. In particular, viruses of the H7 subtype frequently do not induce strong antibody responses following immunization.ObjectivesTo evaluate whether poor immunogenicity of H7 viruses is an intrinsic property of the H7 hemagglutinin.MethodsWe compared the immunogenicity, in naïve mice, of purified recombinant HA from two H7 viruses [A/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Avian influenza viruses, notably H5 and H7 subtype viruses associated with human infection, have been found to be poorly immunogenic in mammals, 61 leading to difficulties in identifying mild or asymptomatic cases. Although supportive evidence is lacking, it is possible, in conjunction with a poorly immunogenic H7 haemagglutinin that infection stemming from ocular exposure, or disease when ocular and not respiratory symptoms are the primary indicator of disease, contributes to this decreased immune activation or depressed serological responses to infection, or both.…”
Section: H7 Viruses Represent a Critical Tool For Unlocking Ocular Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian influenza viruses, notably H5 and H7 subtype viruses associated with human infection, have been found to be poorly immunogenic in mammals, 61 leading to difficulties in identifying mild or asymptomatic cases. Although supportive evidence is lacking, it is possible, in conjunction with a poorly immunogenic H7 haemagglutinin that infection stemming from ocular exposure, or disease when ocular and not respiratory symptoms are the primary indicator of disease, contributes to this decreased immune activation or depressed serological responses to infection, or both.…”
Section: H7 Viruses Represent a Critical Tool For Unlocking Ocular Trmentioning
confidence: 99%
“…46 Unlike HPAI A H5N1 viruses, which frequently elicit heightened induction of proinflammatory mediators, HPAI H7 subtype viruses often elicit delayed and weakened responses in laboratory assays. 61,67 As such, identification of differential induction of host signalling pathways between influenza viruses associated with respiratory disease compared with influenza viruses associated primarily with human conjunctivitis points to potential roles in host responses governing tissue tropism. 47,66 …”
Section: H7 Viruses Represent a Critical Tool For Unlocking Ocular Trmentioning
confidence: 99%
“…Hence, the majority of the human population still lacks protective immunity against H7N9 virus. Although vaccination is the most cost-effective intervention strategy, several independent studies have shown that H7N9 vaccines are poorly immunogenic [4, 5]. Furthermore, the circulation of H5N2 and H5N8 viruses in the United States is threatening the supply of embryonated chicken eggs, the substrate for current egg-derived inactivated and live attenuated influenza vaccines production[6].…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from the fact that human infections with H7 AIVs of both low and high pathogenicity from both Eurasian and North American lineages have been documented, while only Eurasian lineage H5, H6, H9, and H10 AIVs have been documented to cause human cases (reviewed in reference 11). There is also evidence that H7 viruses are less immunogenic than other subtypes, which, from a vaccination perspective, is of particular concern (24)(25)(26)(27). Because H7 viruses appear to stand out from other AIV subtypes in the variety of viruses that can cause disease, it is important to study these viruses in mammalian models to further understand their potential to cause disease.…”
mentioning
confidence: 99%